2018
DOI: 10.1101/416396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of a Distinct Metabolomic Subtype of Sporadic ALS Patients

Abstract: 232

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In addition to genomics and transcriptomics, other innovative omics sciences, including metabolomics, have allowed the identification of specific markers and signatures that can distinguish between ALS patients and healthy individuals, as well as stratify SALS patients into different subgroups [ 46 , 47 , 92 , 93 , 94 ]. One striking example was reported in the study of Wuolikainen and colleagues, where ALS patients bearing different SOD1 mutations presented a very distinct metabolic signature (including a decrease in amino acids in the CSF) in comparison to patients without SOD1 mutations (both familial and sporadic cases), and this classification was also observed between homozygous and heterozygous carriers of these ALS genetic variants, correlating with different disease progression patterns [ 46 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to genomics and transcriptomics, other innovative omics sciences, including metabolomics, have allowed the identification of specific markers and signatures that can distinguish between ALS patients and healthy individuals, as well as stratify SALS patients into different subgroups [ 46 , 47 , 92 , 93 , 94 ]. One striking example was reported in the study of Wuolikainen and colleagues, where ALS patients bearing different SOD1 mutations presented a very distinct metabolic signature (including a decrease in amino acids in the CSF) in comparison to patients without SOD1 mutations (both familial and sporadic cases), and this classification was also observed between homozygous and heterozygous carriers of these ALS genetic variants, correlating with different disease progression patterns [ 46 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Similarly, low urate plasma levels were related to a higher risk of developing ALS, years before the onset of symptoms [ 95 ]. In another study, researchers categorized the metabotype of skin-derived fibroblasts from SALS patients into different subgroups characterized by distinct metabotypes, one of them typified by increased trans-sulfuration pathway-derived cysteine to support GSH biosynthesis and glucose hypermetabolism, in comparison with controls and other SALS subgroups [ 47 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…In this context, metabolomics, the scientific study of chemical processes involving metabolites (e.g., sugars, lipids, amino acids, organic acids), represents the downstream of systems biology that links the genome, transcriptome and proteome to patient phenotype, providing an important key tool for discovering potential markers in health or disease (Kumar et al, 2013;Blasco et al, 2016;Lanznaster et al, 2018Lanznaster et al, , 2020Germeys et al, 2019). In the last years, thanks to the development of high-throughput technologies (such as Mass Spectrometry Combined with Liquid and Gas Chromatography), metabolomics studies identified specific metabolic markers and signatures that can discriminate ALS from controls and non-ALS cases, as well as identify distinct subgroups of SALS patients, moving research toward the development of novel targeted personalized treatments (Gross et al, 2018;Lanznaster et al, 2018). In particular, Gross et al (2018) recently identified two subgroups of SALS case fibroblasts displaying distinct metabotropic patterns that were also observed in plasma samples from the same patients, thus providing a basis for stratify SALS patients for appropriate targeted therapies (Gross et al, 2018).…”
Section: Proteomicsmentioning
confidence: 99%
“…In the last years, thanks to the development of high-throughput technologies (such as Mass Spectrometry Combined with Liquid and Gas Chromatography), metabolomics studies identified specific metabolic markers and signatures that can discriminate ALS from controls and non-ALS cases, as well as identify distinct subgroups of SALS patients, moving research toward the development of novel targeted personalized treatments (Gross et al, 2018;Lanznaster et al, 2018). In particular, Gross et al (2018) recently identified two subgroups of SALS case fibroblasts displaying distinct metabotropic patterns that were also observed in plasma samples from the same patients, thus providing a basis for stratify SALS patients for appropriate targeted therapies (Gross et al, 2018). Other metabolite profiling-based studies revealed significantly different metabolic profiles among FALS, SALS and ALS patients carrying different mutations in diseasecausing genes (i.e., C9ORF72, SOD1, TARDBP, and FUS), suggesting the existence of distinct neurodegenerative processes associated with different subtypes of ALS (Wuolikainen et al, 2012;Jääskeläinen et al, 2019;Lanznaster et al, 2020).…”
Section: Proteomicsmentioning
confidence: 99%